The Effect of Governance on Specialist Auditor Choice and Audit Fees in U.S. Family Firms - Srinidhi, Bin N.; He, Shaohua; Firth, Michael (The Accounting Review, 2014)
ABSTRACT Family firms are characterized by less separation between ownership and control (Type 1 agency problem), but greater conflict of interest between controlling insiders and non-controlling outside investors (Type 2 agency problem). Although strong board governance is known to decrease the Type 1 agency problem, its effectiveness in mitigating the adverse consequences of the Type 2 agency problem has not been well documented in the literature. We show that strongly governed family firms are more likely to choose specialist auditors and exhibit higher earnings quality than nonfamily firms. Weakly governed family firms demand lower audit effort and exhibit earnings quality that is no different from that of nonfamily firms. Within family firms, we show that strongly governed family firms choose higher quality audits in the form of a greater use of specialist auditors and higher audit efforts, and exhibit higher earnings quality than other family firms. These findings provide consistent evidence that strong board governance can effectively mitigate the adverse consequences of the Type 2 agency problem on financial reporting and transparency in family firms. Data Availability: The data used are available from the public sources identified in the study.